The contribution of thrombin-induced platelet activation to thrombus growth is diminished under pathological blood shear conditions - Lee, Hannah; Sturgeon, Sharelle A.; Jackson, Shaun P.; Hamilton, Justin R. (Thrombosis and Haemostasis, 2012)
Developing novel anti-platelet therapies is an important clinical strategy for the prevention of arterial thromboses which cause heart attacks and most strokes. Thrombin activates platelets via protease-activated receptors (PARs), and PAR antagonists are currently under investigation as antithrombotics. Yet despite these clinical advances, the importance of PARs to platelet activation during thromboses formed under pathological conditions has not been investigated. To this end, we examined the role of PAR-dependent platelet activation in thrombus formation in the presence of elevated blood shear rates. We used two in vivo thrombosis models and an ex vivo whole blood flow approach in PAR4-/-mice, whose platelets are unresponsive to thrombin, to show that the contribution of PAR-mediated platelet activation to thrombosis is diminished at pathological blood shear rates as a direct result of decreased incorporation of thrombin-activated platelets into growing thrombi. Our ex vivo observations were replicated in human whole blood treated with a PAR1 antagonist. These results define a novel, shear-regulated role for thrombin/PAR-dependent platelet activation during thrombosis and provide important insights into the conditions under which PAR antagonists may best be used for the prevention of acute coronary syndromes.
Keywords: Blood shear; platelets; protease-activated receptors; thrombin; thrombosis